تيسير النحو العربي بين التنظير والتعليم - الأمين, ملاوي (Sciences humaines; Vol. 25 (2012): SCIENCES HUMAINES, 2014)
كثيرة هي محاولات الدارسين المحدثين لتجديد النظر النحوي القديم المعروفة بجهود التيسير، ومع الإقرار بجهد أصحابها والاعتراف بفضلهم إلا أنها عجزت عن تقديم بديل شامل للنموذج النحوي التراثي،ولعل مرد ذلك إلى عدم الاهتمام ببيان نظرية النحو والخلط بين مبادئ التنظير ومتطلبات التدريس؛ إذ يتطلب الاجتهاد النحوي الوقوف على معالم النظرية النحوية مقدمة للتجديد والفصل بين النظرية والتطبيق تمهيدا للتيسير.   A lot of attempts have been presented by modernists to renew the vision toward traditional grammar; however they did not succeed to. This goes back to the neglect ion of the theoretical grammar and the interference between theoretical principles and teaching needs and this is due to the fact that linguistic competence needs to give priority and Importance to theory and distinguish between this latter and practice to facilitate the teaching process.